Indole alkaloid glucosides from the roots of Isatis indigotica. Issue 1 (2nd January 2016) - Liu, Yu-Feng; Chen, Ming-Hua; Lin, Sheng; Li, Yu-Huan; Zhang, Dan; Jiang, Jian-Dong; Shi, Jian-Gong
Abstract: Five new indole alkaloid glucosides named isatindigotindolosides A-E (1–5 ), along with three known analogs (6–8 ), were isolated from an aqueous extract of the Isatis indigotica roots. Their structures including the absolute configurations were determined based on comprehensive spectroscopic data analysis, combined with chemical methods and electronic circular dichroism spectra calculations. In the preliminary assays, compounds1, 6 and7 showed antiviral activity against influenza virus A/Hanfang/359/95 (H3N2) with IC50 values of 14.6–33.3 μM. Compound1 also exhibited inhibitory effect against nitric oxide (NO) production in microglial cell BV2 with an inhibition ratio of 93.0% at 10 μM.